Determination Of Coefficient For Pm10 Monitoring Using An Optical Direct Reading Instrument And Beta Attenuation Monitor - Mohtar, Zul Azmi (2013)
This research compares PM10 mass concentration record generated by two types of aerosol monitoring devices, the Optical Direct Reading Monitor (ODRM) and the BAM1020, were collocated outdoors at Perai and Seberang Jaya. ODRM records were adjusted to predict Beta Attenuation Monitor (BAM) with a correction factor k derived from co-located BAM and ODRM at a research site to make data comparable in real terms. Predicted BAM records were obtained using quantile regression. Performance indicator such as Coefficient of Determination (R2), Index of Agreement (IA), Normalised Absolute Error (NAE) and Root Mean Square Error (RMSE) were used to measure the accuracy of the predicted BAM and actual BAM. The k was successfully identified for Five Groups of Percentile and Seven Groups of Percentile. For both methods, monitoring records were treated using two techniques and named as Clean Record and Original Record. Clean Records removed the first two days records and concentrations lower than 10 μg/m³. For Original Record, only the first two days (48 hours) records were removed. Positive significant correlation was found between PM10 and temperature at all station using ODRM and BAM. However, for correlation between PM10 and RH, all stations showed negative correlation except Perai station using ODRM (0.901). The equation model used for predicted BAM is . pred BAM    kx which is  . is constant value and x is observed ODRM. Five Groups of Percentile using Clean Record is the best for both stations. R2 value for Five Groups of Percentile for Perai is 0.9170 and 0.9422 for Seberang Jaya compared with Seven Groups of Percentiles that is 0.8795 for Perai and 0.8402 for Seberang Jaya. Hence, simple optical direct reading instrument can be used as a surrogate to measure PM10 following statistical calibration by using quantile regression.